Single Term Concepts from English Translated Qur’an Using Statistical Methods - Ismail, Rohana; Abd. Rahman, Nurazzah; Abu Bakar, Zainab (International Journal of Engineering and Technology, 2018)
Ontology is essential for the success of knowledge based systems because it has the opportunity to share vocabulary, integrate knowledge easily and discover new instances or relations.Â However, the development of ontology via manual is time consuming and tedious task. Thus, ontology learning comes to play it roles. The ontology learning tries to extract ontological elements to support the ontology development. Concept extraction is one of the important tasks in ontology learning. The Hajj domain of Quranic study, concepts have not fully discovered. Hence, this paper tries to discover concepts by extracting the single terms from Qurâ€™an translated version. It provides result on extracting the single terms as concepts by using statistical methods. Apart from that, it has been experimented for English Translated Quran by Hilali Khan. Result shows that the performance of using tf method as a statistical method is significant with the f-measure value is 0.509. Based on the tf, the comparisons have been made for other statistical methods such as tfidf, Avetf and Ridf.Â